Dance for Parkinson, multifaceted experiences of persons living with Parkinson’s Disease - Ingrid Andreasson; Ann Björkdahl; Sofi Fristedt; Paula Bergman; Katarzyna Filipowicz; Ida-Klara Johansson; Iolanda Santos Tavares Silva (Scandinavian Journal of Occupational Therapy, 2024)
Background Dance classes for people with Parkinson’s Disease (PD) are offered worldwide; however, further studies are needed to explore patients’ experiences of how dance affects well-being.Purpose To explore how Dance for Parkinson (Dance for PD) is experienced, and how it contributes to the well-being and health of participants in Sweden.Methods This qualitative study collected data from four focus groups. Participants were asked how dance classes impacted their well-being, and their ability to perform activities of daily life. The focus groups were recorded and transcribed. Data were analysed using content analysis, meaning units were coded, and codes were coalesced into categories from which themes were abstracted.Results Dance for PD provided a multifaceted experience related to social relationships, aesthetic context, feelings of wellbeing and the physical experience of dancing. The main theme contained four sub-themes: Connectedness, Pleasure and glamour, Well-being in mind and body and Customized movements.Conclusion The present study highlights that health and well-being are improved by Dance for PD. It is an enjoyable activity that meets the specific needs of persons living with the consequences of PD and should therefore be promoted by occupational therapists.